The Coherent Approach In Teaching Arabic In Theory And Practice - Falah, Moch. Fajarul; Hikmah , Melda; Hidayatullah, Wahyu (EL-MAQALAH : Journal of Arabic Language Teaching and Linguistics, 2024)
Curriculum organization is a crucial aspect in developing a curriculum to achieve optimal educational goals. One model of curriculum organization that can be applied is the correlated curriculum or correlated learning. This study aims to explore the application of correlated curriculum in formal education in Indonesia. The research method used is a qualitative approach with a case study design. Participants in this study include teachers, school principals, curriculum developers, and education department representatives from several high schools that implement correlated curriculum. Data were collected through interviews, observations, and document analysis, using data source triangulation to ensure data validity. Correlated curriculum is an approach to curriculum development where various subjects are interconnected and support one another. This concept aims to show the relationship between various fields of study and integrate knowledge from various subjects so that students can see the connections and relevance between subjects. Although there has been no specific and comprehensive implementation of correlated curriculum in Indonesia, there are efforts that reflect a tendency to link various subjects in the curriculum and learning process, such as thematic integrated approaches in elementary schools and cross-subject learning materials in lesson plans and curriculum frameworks.